Inflammatory cytokines and nuclear factor-kappa B activation in adolescents with bipolar and major depressive disorders. (30th July 2016) - Miklowitz, David J.; Portnoff, Larissa C.; Armstrong, Casey C.; Keenan-Miller, Danielle; Breen, Elizabeth C.; Muscatell, Keely A.; Eisenberger, Naomi I.; Irwin, Michael R.
Abstract: Adults with bipolar disorder (BD) and major depressive disorder (MDD) have higher circulating levels of proinflammatory cytokines than healthy controls. However, it is not known whether pediatric-onset patients with BD or MDD show increases in levels of inflammation or activation of nuclear factor kappa B (NF-κB), a key transcription factor in inflammatory signaling. Circulating levels of inflammatory cytokines, as well as spontaneous and stimulated levels of activated NF-κB in total peripheral blood mononuclear cells, monocytes and lymphocytes were measured in adolescents with BD (n=18), MDD (n=13), or no psychiatric history (n=20). Participants had a range of mood symptoms at time of testing. Adolescents with BD had significantly higher spontaneous levels of NF-κB in peripheral blood mononuclear cells, monocyte and lymphocyte populations, and higher plasma levels of IL-1β than healthy controls. Following stimulation with recombinant human TNF-α, participants with BD and MDD both had greater increases in NF-κB in monocytes than controls. Further, greater stimulated increases of NF-κB in monocytes were associated with the current severity of depressive symptoms. The results are limited by the small sample and cross-sectional design. Interventions that target early immunological dysregulation should be examined in relation to long-term outcomes in youth with bipolar and depressive disorders. Clinical Trial registration information: Early Intervention for Youth at Risk for Bipolar Disorder, https://clinicaltrials.gov/ct2/show/NCT01483391 . Highlights: Few studies have examined immunological functioning in youths with bipolar disorder. Bipolar, depressed, and healthy adolescents were compared on inflammatory measures. Bipolar adolescents had higher levels of NF-κB and IL-1β than controls. Immune dysregulation may be a target for early intervention in bipolar disorder.